Latino, Hispanic, or of Spanish Origin+ Identified Student Leaders in Medicine Recognizing More Than 50 years of Presence, Activism, and Leadership - Sánchez, John Paul; Rodriguez, Donald (Sustainable Development Goals Series,, 2024)
This book explores the rich history and current state of the Latina, Latino, Latinx, Latine, Hispanic, or of Spanish Origin+ (LHS+) community's representation, activism, and leadership within American medicine. It meets the demand for a reference that highlights both the underrepresentation and growth of the LHS+ community in medicine, especially as the LHS+ population now represents the largest non-white ethnic group in the United States. It examines the LHS+ community's unique health issues and disparities, its ongoing efforts to address such health issues, and its approaches and challenges to developing generations of physicians and healthcare leaders. An Open-Access reference and Sustainable Development Goals Series volume, this book serves as an informative and inspirational resource for educational programming, drafting of policies and procedures, and institutional strategic planning. Across 16 chapters, LHS+ community members and leaders share their unique experiences in pursuing medical careers, using compelling narratives crafted to inspire more LHS+-identified college students to become healthcare professionals and leaders themselves. Additionally, chapters describe several ways in which non-LHS+ identified colleagues can better prepare themselves and their respective institutions to advance health equity for LHS+ communities, support LHS+ learners at all stages of medical education, and bolster current and future LHS+ faculty and senior academic leaders. Latino,Hispanic, or of Spanish Origin+ Identified Student Leaders in Medicine: Recognizing More Than 50 Years of Presence, Activism, and Leadership is a unique and timely book meant to unite and empower current and future physicians through service, mentorship, and education for the benefit of historically underserved communities in the U.S. and beyond. .